Pengaruh Kepemimpinan Kepala Sekolah Dan Pengelolaan Kepegawaian Terhadap Penanggulangan Stres Guru Pada Sekolah Menengah Atas Di Sub Rayon 11 Parung Kabupaten Bogor - Muhammad Mudzakkir; EE. Junaedi Sastradiharja (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2019)
This research aims to know and test the empirical data related to the influence of the leadership of the principal and the management of personnel against the management of stress teachers separately as well as simultaneously. In this research, the authors use quantitative methods with the corelasional approach towards quantitative data obtained from research object i.e. High school teachers in sub 11 rayon parung bogor Regency. The sample of this research is as much as 104 respondents out of a total population of 140 private high school teacher in sub 11 rayon parung bogor Regency. Data collection is done using an engineering question form/questionnaire. This type of analysis is the analysis of correlation and regression are spelled out in the descriptive. The results of this research are: First, There is a positive and significant influence among the leadership of the principal against stress management teacher the correlation coefficient of 0.660 and coefficient of determination R2 of 0.436 which give influence on stress management teacher of 43.6%. and the remaining 56.4% determined by other factors. Koefesien regression obtained Ŷ = 55.886 + 0.531X1 means that every increase of one unit of score leadership principals affect improvement score of teacher stress management 0.531. Second, There are a positive and significant influence between the management of the staffing against stress management teacher with the correlation coefficient of 0, 694 and the coefficient of determination R2 of 0, 481 that gives the effect on stress management teacher of 48.1% and the rest that is 51.9% determined by other factors. Koefesien regression obtained Ŷ = 50.334 + 0.572X2 means that each increase of one unit of score management staffing affects improvement score of teacher stress management0.572. Third, There are a positive and significant influence among the leadership of the principal and management staffing together-the same against stress management teacher with koefisen correlation = 0.706 and koefesien determination of R2 of 0 , 499 that influence is simultaneously against stress management teacher of 49.9% and the rest i.e. 50.1% is determined by other factors. Koefesien regression obtained Ŷ = 47.229 + 0.205X1+ 0.394X2means every one unit increase in score independent leadership of the principal and the management of personnel in simultaneously affect the improvement of teacher's stress management score 0.205+ 0.394 = 0.599.